Pengaruh Kesadaran Wajib Pajak dan Modernisasi Administrasi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Moh. Fikri Fauzi; Elly Halimatusadiah (UNISBA Press, 2022)
Abstract. Taxes have a big contribution to development in Indonesia because taxes are state revenues. Compliance with paying motor vehicle taxes is very important to increase local revenue. The purpose of this study was to determine the effect of taxpayer awareness and modernization of tax administration on motor vehicle taxpayer compliance at the Pajajaran SAMSAT Office in Bandung City. This study uses a verification method with a quantitative approach. Data collection techniques used were questionnaires with 50 motor vehicle taxpayers registered at the SAMSAT Pajajaran office in Bandung. The object of this research is taxpayer awareness, tax administration modernization, and motor vehicle taxpayer compliance. The data used in this study using primary data obtained from the results of filling out questionnaires by respondents of motorized vehicle taxpayers registered at the SAMSAT Pajajaran office in Bandung City. The statistical technique used in data analysis is multiple regression method with SPSS version 23 application. Based on the analysis, it is known that taxpayer awareness, tax administration modernization, and taxpayer compliance at the SAMSAT Pajajaran Office, Bandung City have been going well. Mandatory awareness and compliance of motor vehicle taxpayers in the